Socio-behavioural factors and early childhood caries: A cross-sectional study of preschool children in central Trinidad. - NUNN, JUNE (My University, 2013)
Background Early childhood caries (ECC) is a public health problem due to its impact on children’s health, development and well being. Little is known about early childhood oral health in the West Indies or the influence of social and behavioural factors on the prevalence and severity of early childhood caries in this preschool population. The aims of this study were to describe the prevalence and severity of ECC in preschool children in a region of central Trinidad and to explore its relationship with social and behavioural factors. Method A cross-sectional survey was undertaken on children aged 3-5 years-old from a random sample of preschools in central Trinidad. Oral health examinations were conducted for children for whom parental consent was given, using WHO criteria (visual diagnosis / cavitation at d3). A self-reported questionnaire was distributed to all parents and caregivers. Variables included socio-demographics, oral health knowledge, attitudes and behaviours, visible caries experience and treatment need. Results 251 children were examined, 50.2% were male with a mean age of 3.7 years (SD 0.67) and 71% were of Indian ethnicity. The prevalence of ECC was 29.1% and the prevalence of severe early childhood caries (S-ECC) was 17.5%. 29.9% of children had some treatment need, with 12% in need of urgent care or referral. Poisson generalized linear mixed model analysis found a higher rate of visible caries experience for children who ate sweet snacks more than twice a day (p < 0.001), had poorer parental dental health ratings (p < 0.0001), a previous dental visit (p < 0.0001) and difficulty finding dental care (p < 0.001). Conclusion The prevalence and severity of ECC in central Trinidad was related to oral health behaviours and access to dental care. Oral health promotion should include more supportive and practical advice for parents and caregivers of preschool children along with improved access to dental care to enable primary prevention and management of ECC.
PUBLISHED
Keywords: Early childhood caries; Preschool children; Oral health behaviour; West Indies